2022
DOI: 10.1519/ssc.0000000000000732
|View full text |Cite
|
Sign up to set email alerts
|

Considerations to Optimize Strength and Muscle Mass Gains Through Flywheel Resistance Devices: A Narrative Review

Abstract: Flywheel (FW) resistance training is a valid and time-efficient method to improve force production and muscular hypertrophy. However, no definitive consensus exists regarding FW parameters for optimizing chronic training responses. Therefore, this review aims to examine the FW training literature and provide evidence-based conclusions and practical applications for practitioners. This review reports that FW resistance training is a valid strategy to improve force, power, and hypertrophy responses; however, dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…It was recently reported that flywheel training frequency prescribed in professional soccer was mostly in line with current guidelines (1–2 sessions per week) ( 13 , 17 ). Additionally, flywheel training is perceived to be an effective training method to enhance strength ( 13 ), which is also in agreement with the literature ( 4 , 18 ). Nonetheless, differences in perceptions and application of flywheel training amongst soccer practitioners differed from current evidence-based practice and some beliefs were not founded on strong evidence ( 13 ).…”
Section: Introductionsupporting
confidence: 88%
“…It was recently reported that flywheel training frequency prescribed in professional soccer was mostly in line with current guidelines (1–2 sessions per week) ( 13 , 17 ). Additionally, flywheel training is perceived to be an effective training method to enhance strength ( 13 ), which is also in agreement with the literature ( 4 , 18 ). Nonetheless, differences in perceptions and application of flywheel training amongst soccer practitioners differed from current evidence-based practice and some beliefs were not founded on strong evidence ( 13 ).…”
Section: Introductionsupporting
confidence: 88%
“…0.025-0.050 kg•m 2 ) to be appropriate when the objective is to promote a higher movement velocity and power output [48,180,181], whereas higher inertial loads (i.e. > 0.050 kg•m 2 ) may be more suitable to develop strength-related characteristics [182,183]. In the study by Westblad et al [173], inertial loads of between 0.025 and 0.050 kg•m 2 were prescribed, which was likely too great for this population, especially when considering that other investigations have recently demonstrated the inability of young athletes to translate the energy absorbed during the eccentric phase of jump tasks into concentric performance [111,184].…”
Section: Sprint and Cod Performancementioning
confidence: 99%